Correlation between body temperature, blood pressure and plasmatic nitric oxide in septic patients - Flávia Helena Pereira; Marcelo Eduardo Batalhão; Evelin Capellari Cárnio (Universidade de São Paulo, 2014)
OBJECTIVE: to investigate whether there is a relationship between plasmatic levels of nitrate, body temperature, and blood pressure values in patients with sepsis, severe sepsis and septic shock. METHOD: prospective observational study performed in a Brazilian hospital; data were collected from July to December 2009. Thirty blood samples were obtained from a total of 29 patients. Blood samples (10ml) were collected for subsequent laboratory analysis to determine nitrate levels in the plasma. RESULTS: nitric oxide synthesis is increased in patients with septic shock, and is inversely correlated to the body temperature values. CONCLUSION: these data show that the measurement of body temperature and the observation of hypothermic conditions in septic patients could be important to guide the nursing regarding the evolution of individuals with sepsis to septic shock.